Cannabigerol (CBG): A Comprehensive Review of Its Molecular Mechanisms and Therapeutic Potential - Shijia Li; Weini Li; Naseeb Kaur Malhi; Junwei Huang; Quanqi Li; Ziwei Zhou; Ruiheng Wang; Jiangling Peng; Tong Yin; Honggen Wang (Molecules)
Cannabigerol (CBG), a non-psychoactive cannabinoid found in cannabis, has emerged as a promising therapeutic agent with a diverse range of potential applications. Unlike its well-known counterpart tetrahydrocannabinol (THC), CBG does not induce intoxication, making it an attractive option in the clinic. Recent research has shed light on CBG’s intriguing molecular mechanisms, highlighting its potential to modulate multiple physiological processes. This review delves into the current understanding of CBG’s molecular interactions and explores its therapeutic power to alleviate various conditions, including cancer, metabolic, pain, and inflammatory disorders, amongst others. We discuss how CBG interacts with the endocannabinoid system and other key signaling pathways, such as CB1, CB2, TPR channels, and α2-adrenoceptor, potentially influencing inflammation, pain, neurodegeneration, and other ailments. Additionally, we highlight the ongoing research efforts aimed at elucidating the full spectrum of CBG’s therapeutic potential and its safety profile in clinical settings. Through this comprehensive analysis, we aim to provide a deeper understanding of CBG’s role in promoting human health and pave the way for future research endeavors.